Experimental study and modeling of fatigue life prediction of plain weave carbon/polymer composite under constant amplitude loading. (4th July 2017) - Ji, Qinghui; Zhu, Ping; Lu, Jiahai; Zhu, Chao
Abstract : For fiber-reinforced composites, the anisotropy and the tension-compression asymmetry have very important influence on fatigue performance. The quasi-static and fatigue mechanical behavior of plain weave laminates of carbon/polymer composites were experimentally investigated in this paper. The quasi-static and stress-controlled fatigue tests were carried out on the servo-hydraulic material testing machine. Fracture failure surfaces were observed in micro-mechanism with scanning electron microscopy. A phenomenological and nonlinear constant life diagram (CLD) model was developed based on quasi-static strength and S – N curve data-sets of different stress ratios. The relationship between six parameters of the proposed model and the failure cycles was studied. The fatigue experimental results showed that the fatigue failure type changed from tensile mode to compressive mode at nearby stress ratio R  = −0.2. A satisfactory agreement between the predicted value of cycle life and experimental data was observed. The results indicated that the fatigue performance was adequately described by the Basquin S – N formulation and proposed CLD.